2013
DOI: 10.1002/ange.201209513
|View full text |Cite
|
Sign up to set email alerts
|

Charge Dynamics in A Donor–Acceptor Covalent Organic Framework with Periodically Ordered Bicontinuous Heterojunctions

Abstract: Lichte Momente: Einblicke in den Mechanismus der photochemischen Vorgänge und der Ladungsdynamik eines kovalenten, organischen Donor‐Akzeptor‐Gerüsts wurden mithilfe zeitauflösender transienter Absorptions‐ und Elektronenspinresonanz‐Spektroskopie erhalten (siehe Bild). Das organische Gerüst ermöglicht einen ultraschnellen Elektronentransfer sowie eine weitreichende Ladungsdelokalisierung und eine Langzeit‐Ladungstrennung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 39 publications
0
74
0
1
Order By: Relevance
“…COFs have attracted a lot of interest for their diverse applications, including gas separation and storage,7, 8 catalysis,9, 10 and optoelectronic devices 4. 11 On the other hand, the reversible reactions can lead to instability of the COF structure. Thus, rational design and optimization of the linkages in COFs have become a focus for research in the field to enhance COF stability.…”
Section: Methodsmentioning
confidence: 99%
“…COFs have attracted a lot of interest for their diverse applications, including gas separation and storage,7, 8 catalysis,9, 10 and optoelectronic devices 4. 11 On the other hand, the reversible reactions can lead to instability of the COF structure. Thus, rational design and optimization of the linkages in COFs have become a focus for research in the field to enhance COF stability.…”
Section: Methodsmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are a class of porous organic polymers that have attracted tremendous interest in various fields, such as gas adsorption and storage,, catalysis, sensing, and photovoltaics . They do not only exhibit exceptional properties (such as permanent porosity, high surface areas, and easily‐tunable frameworks) but also, their fully organic nature may result in an improved filler–polymer interaction, avoiding the formation of nonselective defects upon MMM preparation .…”
Section: Figurementioning
confidence: 99%
“…[18] In addition, Saha and co-workers have shown that during the interaction with strong basic anions, such as fluoride, an electron-transfer (ET) process between the anions and the electron-deficient NDI occurs, which can take place thermally or is just photoinduced (PET), depending on the position of the frontier molecular orbitals (FMOs) of the NDI and anion. [19] Besides the donor-acceptor complexes, organic scaffolds [20] and supramolecularly organized systems have been created through appropriate functionalization of NDIs. Amino acid functionalized NDI derivatives were used to build-up helical nanorods that are held together through hydrogen bonding and can function, for example, as receptors for C 60 .…”
Section: Introductionmentioning
confidence: 99%